Sequence Analysis of ITS Ribosomal DNA in Five «Phaeoacremonium» Species and Development of a PCR-Based Assay for the Detection of «P. chlamydosporum» and «P. aleophilum» in Grapevine Tissue - Emanuela Bertelli; Giuseppe Surico; Stefania Tegli (Phytopathologia Mediterranea, 2006)
Phaeoacremonium aleophilum and P. chlamydosporum are two recently described mitosporic fungi that are involved in the development of symptoms of esca disease and of a decline of young grapevines previously named “black goo”. The Internal Transcribed Spacers (ITS) 1 and 2, plus the interveining 5.8S gene, of ribosomal DNA (rDNA) of representative isolates of the two species and, for comparison, of isolates of the congeneric species P. angustius, P. inflatipes and P. rubrigenum were amplified by Polymerase Chain Reaction (PCR) using the ITS4 and ITS5 universal primers. The size of the entire ITS region (ITS1-5.8S-ITS2), plus the 3’ end of 18S rDNA and the 5’ end of 28S rDNA, was estimated to be about 620 bp, on gel electrophoresis, for all the Phaeacremonium species tested. Eleven restriction enzymes were used singularly in the digestion of the ITS region of 30 isolates of P. chlamydosporum, 16 of P. aleophilum, 2 of P. angustius, 2 of P. inflatipes and 1 of P. rubrigenum. No length-polymorphism could be detected within species (except for P. aleophilum), but there were quite strong differences between species. The PCR products of ITS region of ten representative isolates for the five Phaeoacremonium species were sequenced, and the sequences aligned and compared. Two main groups were clearly distinguishable, one formed by P. chlamydosporum, and the other by P. aleophilum, P. angustius, P. inflatipes and P. rubrigenum, with an homology between the two groups ranging from 64.5% to 66.5%. The sequences of ITS region were used to design two pairs of primers, Pal1N/ Pal2 and Pch1/Pch2, each of which was subsequently shown to be specific for the amplification of predicted-size fragments from genomic DNA of P. aleophilum and P. chlamydosporum, respectively. The identity of the amplified fragments was confirmed by sequencing. The primer pairs were further tested using as template DNA extracted from healthy grapevines and from other fungi commonly isolated from esca-diseased grapevine plants but no amplification was observed. The PCR protocol was shown to be quite sensitive (10 pg of DNA) and able to specifically detect P. chlamydosporum and P. aleophilum in artificially inoculated grapevine plants.